Project-Oriented Problem-Based Learning and Innovation within TVET Ruminant Education - Yin Liangyu; Khairul Anuar Abdul Rahman; Nuramiratul Hafizah Jurime (Journal of Technical Education and Training, 2024)
Malaysia is seeing a decrease in its self-sufficiency rate for beef, buffalo, goat, and sheep flesh due to a scarcity in supply. Even while the government has taken steps to reduce reliance on imports, the problem remains. The lowest number of TVET graduates are produced by the agricultural and veterinary sectors, which has a negative impact on both food safety and productivity. As a result, Project-Oriented Problem-Based Learning (POPBL) in TVET for ruminant education cultivates practical problem-solving and hands-on skills in a real-world vocational experience. This issue is exacerbated by the mismatch between institutions and industry, as well as the competency of lecturers. Consequently, the objective of this investigation is to investigate the constructs, sub-constructs, and components of institutional facilities, as well as the expertise of lecturers, in order to facilitate the education of ruminants in vocational colleges in Malaysia. The researcher employed a qualitative approach and a phenomenological study design. A purposive sampling technique is employed to conduct a semi-structured interview with five administrators of ruminant livestock farms in order to gather data. The study’s findings indicate that the researcher generated three constructs, 15 sub-constructs, and 59 elements that pertain to institutional facilities, lecturer abilities, and lecturer knowledge. The implications of this study have the potential to assist a variety of stakeholders, including students, lecturers, Malaysian Vocational College institutions, and the government or policy makers, in the development of more effective strategies for the empowerment of technical and vocational education in the field of ruminant livestock.